Belimbing Wuluh (Averrhoa bilimbi Linn.) Leaf Powder as the Natural Repellent Against Meat Fly (Genus sarcopaga) - Wahyuni, Denai; Sari, Wulan (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Efforts are often made to control meat flies with chemical insecticides, but they harm humans, the environment, and other organisms. We use belimbing wuluh leaf as a natural repellent in controlling meat flies. The purpose of this study is to determine the effect of belimbing wuluh leaf powder as a natural repellent and the number of effective doses against meat fly. Using 15 samples at each dose of 1 gr, 2 gr, 3 gr, 4 gr, 5 gr, negative control without powder, positive control with Top Killer powder, performed four repetitions every 10 minutes of observation for 60 minutes. Kolmograv-Smirnov normality test, P-value 0.200 0.05 means that the data for each group is normally distributed. Variant test, P-value 0.066 0.05, so there was a group that had homogeneous data variants, an ANOVA test resulted in a Sign value of 0.001. There is an effect of the belimbing wuluh leaf powder dose as the repellent of meat flies. The 5-gram dose is the most effective as a natural repellent of meat flies (Genus Sarcopaga).